PENGARUH VIDEO VIRTUAL TOUR INSTALASI BEDAH SENTRAL (IBS) TERHADAP MOTIVASI BELAJAR MAHASISWA KEPERAWATAN ANESTESIOLOGI UNIVERSITAS ‘AISYIYAH YOGYAKARTA - TJ, Aisyah Ruby Endima; Purnamasari, Vita (Jurnal Ilmiah Kesehatan, 2024)
Purpose: The study aims to find out whether there is an effect of providing a virtual tour video of the Central Surgery Room on the learning motivation of Anesthesiology Nursing students at Universitas ‘Aisyiyah Yogyakarta. Methods: The research used an experimental type of study with a one-group pretest and posttest design. The population in this study were the 3rd-semester Diploma IV students of the Anesthesiology Nursing program. The sampling technique used was simple random sampling totaling 64 respondents. The instrument was a learning motivation questionnaire. Data analysis was done using the Wilcoxon test. Results: Before being given the virtual tour video, most respondents were at a moderate level of motivation with a mean of 54.41 and after being given the treatment, the majority of respondents were at a high level of motivation with a mean of 69.90. The Wilcoxon test results showed a p-value of 0.000, so the p-value was <0.05. Conclusion: There is an effect of the virtual tour video of the Central Surgery Room on the learning motivation of Anesthesiology Nursing students at Universitas ‘Aisyiyah Yogyakarta.